Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XXII): Clarifying morphological distinction between D. drepanocentrum and D. umbrosum and synonymizing D. umbrosoides with D. drepanocentrum - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Based on critical observations on herbarium specimens (including type material), we demonstrate that Delphinium drepanocentrum (Ranunculaceae), an eastern Himalayan species distributed in Bhutan and China (southern Xizang), is most readily distinguishable from D. umbrosum, a species endemic to northwestern Yunnan, China, by an array of morphological characters, particularly by the indumentum on plant body. Our results support the treatment of D. drepanocentrum as an independent species. Moreover, some collections from Cona in southern Xizang previously cited as D. umbrosum var. drepanocentrum or misidentified as D. umbrosum subsp. drepanocentrum on the determination slips are determined not to belong to D. drepanocentrum, but represent a hitherto undescribed species. Furthermore, D. umbrosoides, described recently from Xizang, is determined to be conspecific with D. drepanocentrum and thus is synonymized herein. Finally, we pointed out that D. umbrosum var. hispidum is identical with D. omeiense, a species distributed in southwestern Sichuan and northeastern Yunnan, China.